Cutaneous Metastasis and Rectum Neoplasia: Case Report - Pretto, Daiane (2020)
Introduction: Skin metastases are neoplasms that affect the dermis or subcutaneous cell tissue and may be an indicator of an unknown neoplasm with a poor prognosis. Skin metastases in rectal adenocarcinoma are considered rare. Case report: An 80-year-old woman, hypertensive and diabetic, had abdominal pain and hematochezia, reporting a family history of cancer. Colonoscopy was performed with biopsy results for adenocarcinoma. One year later, she received neoadjuvant therapy and concomitant radiation therapy for four months, with good response to treatment. However, she reported a fast-growing mandibular lesion, with the gastrointestinal tract as the primary site according to the biopsy. In reassessment CT scans, several small nodules in subcutaneous tissue of the lower abdomen, breast and lung were also diagnosed. A new biopsy of the breast nodules and immunohistochemistry were performed, procedures that suggested the rectum as the primary site of the lesions. Therefore, palliative chemotherapy was started and the patient presented a satisfactory response to skin lesions in the second cycle of antineoplastic treatment. The project was approved by the Institutional Review Board of Hospital Pompeia through report the opinion nº 311.052. Conclusion: This case emphasizes that progressive or unresponsive skin lesions after conventional therapy can be the first manifestation of advanced visceral cancer and should be properly investigated. Thus, it is clear that, through an early diagnosis, it is possible to change the prognosis of the disease and its treatment.